Xenotransplantation - New Insights 2017
DOI: 10.5772/intechopen.69233
|View full text |Cite
|
Sign up to set email alerts
|

Xenotransplantation for Islets from Clinical Side

Abstract: Islet transplantation can eliminate severe hypoglycemia symptoms caused by conventional treatment, and has the advantages of less trauma and complications, which is considered as the most promising treatment for type 1 diabetes mellitus (T1DM). Regulatory guidance is needed for a standard pig source. In section 1, the regulation of medical grade designed pathogen free (DPF) donor pig for clinical xenotransplantation consists of five parts: genetic quality control, microbiological surveillance, formula feeds, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 64 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…We found that the yield of isolated islets was higher in 12‐ to 18‐month‐old pig (data not shown). For porcine islet transplantation into humans, the minimum dose is over 10 000 IEQ/kg per type 1 diabetic patient 34 . This effective dose may even be higher when using pig islets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the yield of isolated islets was higher in 12‐ to 18‐month‐old pig (data not shown). For porcine islet transplantation into humans, the minimum dose is over 10 000 IEQ/kg per type 1 diabetic patient 34 . This effective dose may even be higher when using pig islets.…”
Section: Discussionmentioning
confidence: 99%
“…For porcine islet transplantation into humans, the minimum dose is over 10 000 IEQ/kg per type 1 diabetic patient. 34 This effective dose may even be higher when using pig islets. If the patient needed more islets, islet isolation from 2 or 3 porcine may be necessary 5 because of the lower insulin secretion for cure diabetes in porcine islets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation